(untitled) (Computer systems and information technologies, 2022)
The relevance of research on the use of information technologies to solve applied problems, in particular, financial policy management at the micro level has been revealed in this article. The own definition of the concept of financial policy at the enterprise level has been proposed as a triad of the main content principles, namely: asset management, cash flow management, liability management. It has been established that research in the field of financial policy is mostly theoretical, therefore the development of software module based on the model of solving a practical problem presented in the article is relevant for Ukrainian enterprises. After structurization and determination the list of financial policy tasks, an original improvement of one of the important components in asset management, namely the task of modeling the amount of receivables, has been proposed. In order to obtain the maximum economic effect, it has been proposed to suggest to calculate the optimal level of accounts receivable. Using of the method of approximation of the non-linear dependence of receivables on the credit period, which was initiated by O. I. Luchkov, has been substantiated. The principles of the methodics have been defined, its modification and clarification have been proposed in the direction of the development of methods for calculating the numerical values of all components of the model in the article. This method allows the obtaining the optimal term of the credit period in days and the optimal amount of receivables in monetary terms. Model experiment has been executed to test the model’s operation, during which data from the financial statements of one of the operating enterprises have been used. The obtained results testify to the effectiveness and correctness of the proposed methodics are served as an information basis for management decisions regarding the assessment of the effectiveness of measures to manage the company’s financial policy. The software module has been developed that, based on the results of certain calculations, allows to make quick and well-founded decisions about balancing the structure of assets and liabilities in order to restore financial stability and increase profits.